Covid-19 et handicap mental/Autisme et autres maladies rares - Lumaka, Aimé; DDD-Africa project (My University, 2020)
The Covid-19 is challenging our health systems and showing our limits. Clearly, the world was not prepared to this. Our society and life style need to be adjusted to protect ourselves from this pandemic. The new concept of social distancing has been introduced into our vocabulary and life styles. Considering that implementing social distancing into the Sub-Saharan setting proves to be difficult to educated people, it is understandable that this will be even more challenging for people with developmental disorders, mental retardation, autism or other rare disease. Based on the "Q&A on COVID-19 and Down Syndrome" (https://www.ndss.org/wp-content/uploads/2020/03/2020-COVID19-DS-QA-Abbreviated-03-27-FINAL.pdf), we have hold a discussion session with parents/association leaders from the sector of Autism/mental handicap in DRC and other experts from other French speaking parts of the world. Here we have made available the slides of this meeting. Video recording is available in the supplemental material. Le Covid-19 défie nos systèmes de santé et montre nos limites. De toute évidence, le monde n'était pas préparé à cela. Notre société et notre style de vie doivent être ajustés pour nous protéger de cette pandémie. Le nouveau concept de distanciation sociale a été introduit dans notre vocabulaire et nos styles de vie. Étant donné que la mise en œuvre de la distanciation sociale dans le contexte subsaharien s'avère difficile pour les personnes éduquées, il est compréhensible que cela soit encore plus difficile pour les personnes souffrant de troubles du développement, de retard mental, d'autisme ou d'autres maladies rares. Basé sur le "Q&A on COVID-19 and Down Syndrome" (https://www.ndss.org/wp-content/uploads/2020/03/2020-COVID19-DS-QA-Abbreviated-03-27-FINAL. pdf), nous avons organisé une session de discussion avec des parents / responsables d'associations du secteur de l'autisme / handicap mental en RDC et d'autres experts d'autres régions francophones du monde. Ici, nous avons mis à disposition les diapositives de cette réunion. L'enregistrement vidéo est disponible dans les materiels supplémentaires.
Keywords: autisme et covid-19; Covid-19; Covid-19 et RD Congo; handicap mental et covid; trisomie-21 et Covid-19